2015
DOI: 10.5194/bg-12-6429-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reviews and syntheses: Calculating the global contribution of coralline algae to total carbon burial

Abstract: Abstract. The ongoing increase in anthropogenic carbon dioxide (CO2) emissions is changing the global marine environment and is causing warming and acidification of the oceans. Reduction of CO2 to a sustainable level is required to avoid further marine change. Many studies investigate the potential of marine carbon sinks (e.g. seagrass) to mitigate anthropogenic emissions, however, information on storage by coralline algae and the beds they create is scant. Calcifying photosynthetic organisms, including corall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 106 publications
0
73
1
2
Order By: Relevance
“…For example, Martin et al (2006) reported a seasonal range of 0.68 to 1.48 µmol C (g DW) −1 h −1 for the maerl-forming Lithothamnion corallioides off NW France. Currently, the contribution of coralline algae to global carbon cycles is not well constrained, particularly that of geniculate turfing species (El Haïkali et al, 2004;Van der Heijden and Kamenos, 2015). Given their comparatively high production identified here, our data indicate that geniculate corallines likely play a significant role in coastal carbon cycling, despite their presumably reduced overall benthic coverage compared to maerl-forming or crustose coralline algal species.…”
Section: Production and Respirationmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, Martin et al (2006) reported a seasonal range of 0.68 to 1.48 µmol C (g DW) −1 h −1 for the maerl-forming Lithothamnion corallioides off NW France. Currently, the contribution of coralline algae to global carbon cycles is not well constrained, particularly that of geniculate turfing species (El Haïkali et al, 2004;Van der Heijden and Kamenos, 2015). Given their comparatively high production identified here, our data indicate that geniculate corallines likely play a significant role in coastal carbon cycling, despite their presumably reduced overall benthic coverage compared to maerl-forming or crustose coralline algal species.…”
Section: Production and Respirationmentioning
confidence: 71%
“…C. officinalis NP (assessed from daytime light treatment incubations) and R (assessed from daytime dark treatment and all night-time incubations) were calculated from the difference between initial and final incubation DIC concentrations as follows: where NP and R DAY/NIGHT are net production and respiration during the day or night, respectively (µmol DIC (g DW) −1 h −1 ); DIC is the change in dissolved inorganic carbon concentration during the incubation (µmol DIC kg −1 seawater); v is the incubation chamber volume (L); dw is the dry weight of C. officinalis incubated (g); t is the incubation time (h); and NG is the net calcification rate (µmol CaCO 3 (g DW) −1 h −1 ). NG was estimated using the alkalinity anomaly technique (Smith and Key, 1975;Chisholm and Gattuuso, 1991), whereby TA decreases by 2 equivalents for each mol of CaCO 3 precipitated. Light calcification (assessed from daytime light treatment incubations) and dark calcification (assessed from daytime dark and all night-time incubations) were thus calculated as follows:…”
Section: Physiology Incubationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major groups effected by climate change is calcifying benthic macroalgae (Kroeker et al, 2013). They function as important ecosystem engineers and play a crucial role as an essential structural element in the majority of rocky coastal zones (Benedetti-Cecchi, 2006;Dayton, 1972;van der Heijden & Kamenos, 2015;Johansen, 1981;Jones, Lawton, & Shachak, 1994;Kelaher, Chapman, & Underwood, 2001;Nelson, 2009;Noël, Hawkins, Jenkins, & Thompson, 2009). They function as important ecosystem engineers and play a crucial role as an essential structural element in the majority of rocky coastal zones (Benedetti-Cecchi, 2006;Dayton, 1972;van der Heijden & Kamenos, 2015;Johansen, 1981;Jones, Lawton, & Shachak, 1994;Kelaher, Chapman, & Underwood, 2001;Nelson, 2009;Noël, Hawkins, Jenkins, & Thompson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of C in fjordic sediments was identified as a priority by Syvitski et al (1987), but little progress has been made towards this goal until recently. Our work presented here utilises and extends the joint geochemistry and geophysical methodology developed by Smeaton et al (2016) by applying it to a number of mid-latitude fjords.…”
Section: Introductionmentioning
confidence: 99%